CD73 Rather Than CD39 Is Mainly Involved in Controlling Purinergic Signaling in Calcified Aortic Valve Disease - Kudryavtsev, Igor; Serebriakova, Maria; Zhiduleva, Ekaterina; Murtazalieva, Patimat; Titov, Vladislav; Malashicheva, Anna; Shishkova, Anastasya; Semenova, Daria; Irtyuga, Olga; Isakov, Dmitry; Mitrofanova, Lubov; Moiseeva, Olga; et al. (Frontiers in Genetics, 2019)
The study was aimed to compare composition of peripheral blood T cell subsets and assess their surface expression of CD39 and CD73 ectonucleotidases in patients with severe and moderate aortic stenosis (AS) as well as to evaluate involvement of T cell-mediated immune processes in valve calcification. Study was performed with 38 patients suffering from severe calcified aortic stenosis (SAS), 33 patients with moderate AS (MAS) and 30 apparently healthy volunteers (HV). Relative distribution and percentage of T cell subsets expressing CD39 and CD73 were evaluated by flow cytometry. T helper (Th) and cytotoxic T cell subsets (Tcyt) were identified by using CD3, CD4 and CD8 antibodies. Regulatory T cells (Tregs) were characterized by expression of CD3, CD4 and high IL-2R alpha chain (CD25high) levels. CD45R0 and CD62L were used to assess differentiation stage of Th, Tcyt and Treg subsets. It was found that MAS and SAS patients differed in terms of relative distribution of Tcyt and absolute number of Treg. Moreover, the absolute number of Tcyt and TEMRA subset were significantly higher in SAS vs. MAS patients and healthy volunteers. However, the absolute and relative number of naïve Th, absolute number of Treg were significantly higher in MAS vs. SAS patients, relative number of naïve Tregs was significantly (p<0.01) decreased in SAS patients. It was shown that CD73 expression was significantly higher in SAS vs. MAS patients noted in all EM, CM, TEMRA, and naïve Th cell subsets. However, only the latter were significantly increased (p=0.003) in patients compared to healthy volunteers. SAS vs. MAS patients were noted to have significantly higher percentage of CD73+ EM Tcyt (p=0.006) and CD73+ CM Tcyt (p=0.002). Expression of CD73 in patients significantly differed in all three Treg populations such as EM (p=0.049), CM (p=0.044), and naïve (p<0.001). No significant differences in CD39 expression level was found in MAS and SAS patients compared to HV group. Overall, the data obtained demonstrated that purinergic signaling was involved in pathogenesis of aortic stenosis and calcification potentially acting via various cell types, wherein among enzymes degrading extracellular ATP CD73 rather than CD39 played a prominent role.